The Battered Child Syndrome with a Fatal Outcome - Tüzün, Birgül; Anolay, Nezih; Sözen, Mehmet Şevki; Elmas, İmdat; Akkay, Erdem (The Bulletin of Legal Medicine, 1998)
The battered child syndrome, a behavioral deviation exposing children to harmful, non-accidental and preventable physical treatment of person or people who are responsible to look after them which prevents their physical and psycho-social development and conflicts with the cultural values of the society, is still of great importance today as an undissolved humanity problem. This study is relavent to a 8 years-old girl whose postmortem examination was performed in the Morgue Department of the Council of Forensic Medicine and who had been determined to be highly retardate. During the autopsy of the case, beaten by her stepfather fatally, several regions of the body were found to have invasive lesions of blunt trauma. The case has been presented with a comprehensive analysis to document the physical abuse towards children which is very common in our society, with autopsy results and form of death as well as to determine the approach of physicians to such cases.Key words: Child, Trauma. Battered child
Keywords: child; trauma; battered child